Double blind study of intrathecal beta-interferon in multiple sclerosis: clinical and laboratory results. Issue 7 (July 1990) - Milanese, C; Salmaggi, A; La Mantia, L; Campi, A; Eoli, M; Savoiardo, M; Bianchi, G; Nespolo, A
Abstract : Sixteen patients with clinically definite MS admitted to a double blind randomised controlled trial of intrathecal natural beta-IFN were followed for a mean of 22 months including the six month treatment period. Clinical response, evaluated in terms of relapse frequency and of progression rate, showed an increase in relapse rate in treated patients during the six month treatment period and, overall, no benefit in treated versus placebo patients. Serial evaluations were made of cerebrospinal fluid (CSF) cells, IgG, myelin basic protein and CSF and blood T-cell subsets. A rise in CSF IgG Index, MBP and DR+ cells in IFN-treated patients suggested an activation of intrathecal immune response in treated patients.